A clinical study to compare the effectiveness of dexmedetomidine in attenuating sympathoadrenal response induced by laryngoscopy and endotracheal intubation in smokers versus non-smokers - Shivakumar G; Santhosh MCB; Anusree KM; Umesh NP (Asian Journal of Medical Sciences, 2024)
Background: The process of laryngoscopy and tracheal intubation is potent stressful stimuli that cause sympathetic activation, which is transient. Some of the modalities for attenuation of laryngoscopic and intubation response have been found to be less effective in smokers than in non-smokers. In view of this, the present study was performed to compare the effectiveness of dexmedetomidine in male smoker and non-smoker patients. Aims and Objectives: The aim of this study was to compare the effectiveness of dexmedetomidine in suppressing sympathoadrenal pressor response due to laryngoscopy and endotracheal intubation between smokers and non-smokers. Materials and Methods: This was a hospital-based non-randomized controlled study. Sixty patients were divided into two groups: 30 patients with no history of smoking (Group NS) and 30 patients with a smoking history (Group S). Both groups were received dexmedetomidine 0.75 mcg/kg over 10 min intravenous infusion. Hemodynamic parameters and Ramsay sedation score were measured at perioperative period. Results: Group S patients showed a significant rise in heart rate (HR), systolic blood pressure (SBP), diastolic BP (DBP), mean arterial pressure (MAP), and rate pressure product (RRP) during the immediate post-intubation period, but Group NS showed a decrease in HR, SBP, DBP, MAP and RRP throughout the post-intubation period. Conclusion: Single dose of 0.75 mcg/kg IV dexmedetomidine given over a period of 10 min before the induction of anesthesia is completely effective in attenuating the hemodynamic responses associated with laryngoscopy and intubation in non-smokers, but it is not efficient in smokers.